2011
DOI: 10.1111/j.1471-4159.2011.07511.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk between human mesenchymal stem/progenitor cells (MSCs) and rat hippocampal slices in LPS‐stimulated cocultures: the MSCs are activated to secrete prostaglandin E2

Abstract: Mesenchymal stem/progenitor cells (MSCs) improve functional outcome in a number of disease models through suppression of inflammation. However, their effects on neuroinflammation are unknown. In this study, we show that MSCs suppress endotoxin-induced glial activation in organotypic hippocampal slice cultures (OHSCs). Lipopolysaccharide-stimulated OHSCs activated MSCs to increase the expression of cyclo-oxygenase-2 and produce prostaglandin E2. MSC-derived prostaglandin E2, then suppressed proinflammatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
5
22
0
Order By: Relevance
“…inflammatory (M1-like) into an anti-inflammatory (M2-like) phenotype [26,31,36] mainly through COX-2 mediated production of PGE2 and possibly some other soluble factors [35,37]. Similar PGE2-mediated interaction was also described between other tissue macrophages and MSCs in vitro [12], as well as in vivo [43].…”
Section: Microglia Activation and Effector Functionsmentioning
confidence: 78%
See 1 more Smart Citation
“…inflammatory (M1-like) into an anti-inflammatory (M2-like) phenotype [26,31,36] mainly through COX-2 mediated production of PGE2 and possibly some other soluble factors [35,37]. Similar PGE2-mediated interaction was also described between other tissue macrophages and MSCs in vitro [12], as well as in vivo [43].…”
Section: Microglia Activation and Effector Functionsmentioning
confidence: 78%
“…However, the precise polarization states of microglia in the presence of MSCs under physiological or inflammatory conditions remain largely unknown. In most studies, xenogenic experimental systems were used; that is, cocultures of human MSCs with mouse or rat MGs [26,[31][32][33] and primary microglia were frequently replaced with neoplastic cell lines (BV2 or N9) [34][35][36] or with hippocampal slices [37]. Only two laboratories used autologous mouse [35] or rat [38] primary MGs and MSCs.…”
Section: Au3 Cmentioning
confidence: 99%
“…We initially observed that administration of human MSCs limited injury to the brains of mice after transient global ischemia by modulating neuroinflammation (Ohtaki et al, 2008). We also showed that MSCs suppressed endotoxin-induced glial activation in organotypic hippocampal slice cultures (Foraker et al, 2012). More recently, we reported that some of the therapeutic effects of MSCs can be explained by activation of the cells to express the inflammation modulatory protein TSG-6 in animal models for myocardial infarction (Lee et al, 2009), peritonitis (Choi et al, 2011) and chemical injury of the cornea (Oh et al, 2010).…”
Section: Introductionmentioning
confidence: 84%
“…PI enters only into cells with a damaged cell membrane and is considered to be primarily a marker of necrotic cells [99]. OHCs were placed in media containing 2 μM PI [100, 101] for 2 h prior to imaging. All sections were imaged under identical conditions at prior to (basal) and 2 h following blast injury using a Nikon Eclipse TE2000-U upright fluorescent microscope (Nikon Instrument Inc., Melville, NY, USA) equipped with a digital SPOT camera and software (Spot Imaging Solutions, Sterling Heights, MI, USA).…”
Section: Methodsmentioning
confidence: 99%